Design and commissioning of the non‐dedicated scanning proton beamline for ocular treatment at the synchrotron‐based CNAO facility. Issue 4 (14th February 2019) - Ciocca, Mario; Magro, Giuseppe; Mastella, Edoardo; Mairani, Andrea; Mirandola, Alfredo; Molinelli, Silvia; Russo, Stefania; Vai, Alessandro; Fiore, Maria Rosaria; Mosci, Carlo; Valvo, Francesca; Via, Riccardo; et al.
Abstract : Purpose: Only few centers worldwide treat intraocular tumors with proton therapy, all of them with a dedicated beamline, except in one case in the USA. The Italian National Center for Oncological Hadrontherapy (CNAO) is a synchrotron‐based hadrontherapy facility equipped with fixed beamlines and pencil beam scanning modality. Recently, a general‐purpose horizontal proton beamline was adapted to treat also ocular diseases. In this work, the conceptual design and main dosimetric properties of this new proton eyeline are presented. Methods: A 28 mm thick water‐equivalent range shifter (RS) was placed along the proton beamline to shift the minimum beam penetration at shallower depths. FLUKA Monte Carlo (MC) simulations were performed to optimize the position of the RS and patient‐specific collimator, in order to achieve sharp lateral dose gradients. Lateral dose profiles were then measured with radiochromic EBT3 films to evaluate the dose uniformity and lateral penumbra width at several depths. Different beam scanning patterns were tested. Discrete energy levels with 1 mm water‐equivalent step within the whole ocular energy range (62.7–89.8 MeV) were used, while fine adjustment of beam range was achieved using thin polymethylmethacrylate additional sheets. Depth‐dose distributions (DDDs) were measured with the Peakfinder system. Monoenergetic beam weights to achieve flat spread‐out Bragg Peaks (SOBPs) were numerically determined. Absorbed dose to water under reference conditions was measured with an Advanced Markus chamber, following International Atomic Energy Agency (IAEA) Technical Report Series (TRS)‐398 Code of Practice. Neutron dose at the contralateral eye was evaluated with passive bubble dosimeters. Results: Monte Carlo simulations and experimental results confirmed that maximizing the air gap between RS and aperture reduces the lateral dose penumbra width of the collimated beam and increases the field transversal dose homogeneity. Therefore, RS and brass collimator were placed at about 98 cm (upstream of the beam monitors) and 7 cm from the isocenter, respectively. The lateral 80%–20% penumbra at middle‐SOBP ranged between 1.4 and 1.7 mm depending on field size, while 90%–10% distal fall‐off of the DDDs ranged between 1.0 and 1.5 mm, as a function of range. Such values are comparable to those reported for most existing eye‐dedicated facilities. Measured SOBP doses were in very good agreement with MC simulations. Mean neutron dose at the contralateral eye was 68 μSv/Gy. Beam delivery time, for 60 Gy relative biological effectiveness (RBE) prescription dose in four fractions, was around 3 min per session. Conclusions: Our adapted scanning proton beamline satisfied the requirements for intraocular tumor treatment. The first ocular treatment was delivered in August 2016 and more than 100 patients successfully completed their treatment in these 2 yr.